Absenteeism in Norway - How does the North differ from the rest? A panel data study of the period from 2002 to 2011 - Nyrud, Thomas Christer (UiT Norges arktiske universitet, 2014)
A panel data study of sick leave behavior in the Norwegian population is conducted on a municipality level for the period from 2002 to 2011. Data on sickness insurance usage is fitted against a selection of variables describing different regional characteristics that have been linked with absenteeism in the earlier literature. A basic model for sick leave usage is constructed, and further divided into two slightly different submodels where one is used to analyze sick leave behavior in the 43 northernmost municipalities of Norway, which are located in the counties Troms and Finnmark. The other submodel is used to look at the remaining 385 municipalities. The purpose is to explore why the northern municipalities have an overall higher level of sickness insurance usage than the rest of the country. The performed analysis further looks at men and women separately, as there exists significant gender differences in sick leave usage. The results reveal that especially unemployment, bankruptcies and downsizing are important factors on a national level, but lose explanatory value when zooming in on the north. The average education level is lower among the northern population, and the estimation results strongly suggest that this might be an important part of the answer when asking why sick leave is higher in this part of the country. Further, municipalities with a higher share of female workers between 16 and 25 years of age are found to have lower total sick leave when looking at the 385 municipalities outside of Troms and Finnmark. When shifting focus to the north however, a higher share of this age group is found to predict higher total sick leave usage.